LB14. Efficacy and Immunogenicity of an Ad26.RSV.preF-based Vaccine in the Prevention of RT-PCR-confirmed RSV-mediated Lower Respiratory Tract Disease in Adults Aged ≥65 Years: A Randomized, Placebo-controlled, Phase 2b Study. (4th December 2021) - Falsey, Ann R; Williams, Kristi; Gymnopoulou, Efi; Bart, Stephan A; Ervin, John E; Bastian, Arangassery Rosemary; Menten, Joris; De Paepe, Els; de Boer, Hilde; Vandenberghe, Sjoukje; Chan, Eric; Sadoff, Jerald; et al.
Abstract: Background: Respiratory syncytial virus (RSV) can cause serious lower respiratory tract disease (LRTD) in older adults. Despite a high burden of disease, there is currently no licensed vaccine for RSV. Here, we report the primary efficacy and immunogenicity results from a Phase 2b proof-of-concept trial of an Ad26.RSV.preF-based vaccine for the prevention of RSV-mediated LRTD in adults aged ≥65 years. Methods: CYPRESS (NCT03982199) is a randomized, double-blind, placebo-controlled Phase 2b trial. Adults ≥65 years of age were randomized 1:1 prior to the RSV season to receive an Ad26.RSV.preF-based vaccine or placebo. Symptoms of acute respiratory infection (ARI) were collected through an RSV-specific patient-reported Respiratory Infection Intensity and Impact Questionnaire (RiiQ) and/or by a clinician assessment until the end of the RSV season. The primary endpoint was the first occurrence of RT-PCR-confirmed RSV-mediated LRTD according to any of 3 case definitions: (1) ≥3 symptoms of lower respiratory tract infection (LRTI), (2) ≥2 symptoms of LRTI, or (3) ≥2 symptoms of LRTI or ≥1 symptom of LRTI with ≥1 systemic symptom. The secondary endpoint was the first occurrence of any RT-PCR-confirmed RSV-mediated ARI. Immunogenicity assessments were performed in a subset of approximately 200 participants. Results: A total of 5782 participants (2891 in each study arm) received study treatment (92.5% white, 57.7% female, median age 71 years). Vaccine efficacy was 80% (94.2% CI, 52.2–92.9%), 75% (50.1–88.5%), and 69.8% (43.7–84.7%) for case definition 1, 2, and 3, respectively (all P values < 0.001). Efficacy for any RSV-mediated ARI was 69.8% (95% CI, 42.7–85.1%). In the vaccine arm of the immunogenicity subset, geometric mean fold increase in antibody titers 14 days after vaccination was 13.5 for RSV neutralizing antibodies and 8.6 for RSV prefusion F-specific binding antibodies. Median frequency of RSV-F-specific INFγ T-cells increased from 34 to 444 SFC/10 6 PBMC 14 days after vaccination in the vaccine arm; no relevant changes were observed in the placebo arm. Conclusion: In CYPRESS, the Ad26.RSV.preF-based vaccine was highly effective against RSV-mediated LRTD through the first RSV season and elicited robust humoral and cellular immune responses in adults aged ≥65 years. Disclosures: Ann R. Falsey, MD, AstraZeneca (Individual(s) Involved: Self): Grant/Research Support; BioFire Diagnostics (Individual(s) Involved: Self): Grant/Research Support; Janssen (Individual(s) Involved: Self): Grant/Research Support; Merck, Sharpe and Dohme (Individual(s) Involved: Self): Grant/Research Support; Novavax (Individual(s) Involved: Self): Other Financial or Material Support, Paid DSMB member; Pfizer (Individual(s) Involved: Self): Grant/Research Support Kristi Williams, PhD, Janssen R&D US (Employee) Efi Gymnopoulou, MSc, Janssen Infectious Diseases BV (Employee) Arangassery Rosemary Bastian, PhD, Janssen Vaccines & Prevention BV (Employee) Joris Menten, n/a, Janssen Infectious Diseases BV (Employee) Els De Paepe, MSc, Janssen Infectious Diseases BV (Employee) Hilde de Boer, MSc, Janssen-Cilag (Employee) Sjoukje Vandenberghe, n/a, Janssen Infectious Diseases BV (Employee) Eric Chan, PhD, Janssen Global Services, LLC (Employee) Jerald Sadoff, MD, Johnson & Johnson (Employee, Shareholder) Macaya Douoguih, MD, MPH, Janssen (Employee) Benoit Callendret, PhD, Janssen Vaccines & Prevention BV (Employee) Christy Comeaux, MD, Janssen Vaccines & Prevention BV (Employee) Esther Heijnen, MD, Janssen Vaccines & Prevention BV (Employee)